Front Cover: Comprehensive Human Milk Patterns Are Related to Infant Growth and Allergy in the CHMP Study. Issue 17 (2nd September 2021) - Jiang, Shilong; Pan, Jiancun; Li, Yuanyuan; Ju, Mengnan; Zhang, Wei; Lu, Jing; Lv, Jiaping; Li, Kaifeng
Abstract : Mol. Nutr. Food Res . 2021, 65, 202100011 DOI: 10.1002/mnfr.202100011 The story illustrated in the cover design is that three mothers who are holding or breastfeeding their baby are talking about human milk composition reports which listed their composition details. Three mothers represent three human milk patterns the authors identified; the characteristics of baby are in accordance with the results of our paper. This is reported by Jing Lu, Jiaping Lv, Kaifeng Li and co‐workers in article number 2100011 .